Women and International Humanitarian Law - M Elfan Kaukab; Wiji Yuwono (Metaphor, 2020)
This article aims to describe the extent to which women's human rights and the progress made in protecting women under human rights law will impact international humanitarian law. This study uses a qualitative method with an explanative pattern. The analysis shows that the topic of women and human rights is currently receiving increasing respect as separate areas of international law. The hope is that recognition of women's rights in international humanitarian law will take into account the recognition of women's experiences in armed conflict.